The transformations of the concept of fate in literature - Mogens Bröndsted (Scripta Instituti Donneriani Aboensis, 1967)
In the course of time the literary idea of fate has been subject to a series of transformations which may also be of some interest from the point of view of comparative religion. The primary point of departure is man's dualistic experience of coming up against an exterior power stronger than himself, which thwarts his actions and intentions. This is supposedly the basic element in all primitive religion: the observation of an external power which decisively controls human life. The first phase, then, is religious, whether this power is conceived to be a plurality of spirits or deities or—most primitive of all, according to a recent trend in comparative religion—as a single 'high god'.